Geosystems-indicators of climate change and cultural landscape recovery in Tigireksky Reserve and its protective zone (Altai Krai, Russia). (17th December 2021) - Zolotov, Dmitry; Chernykh, Dmitry; Malygina, Natalia; Biryukov, Roman; Pershin, Dmitry
The paper deals with major trends of landscape dynamics in the northern part of the Tigireksky Reserve. The global warming impact on the study area is confirmed by the ERA5, NCEP-NCAR and CRU TS reanalyses data for 1979-2018. It manifests in decreased atmospheric humidification during the growing season and worsening conditions for forest recovery. We discuss the possibilities of identifying geosystems-indicators for monitoring of climate change and cultural landscape recovery based on the analysis of the author's large-scale landscape map.